Deletion of diacylglycerol-responsive TRPC genes attenuates diabetic nephropathy by inhibiting activation of the TGFβ1 signaling pathway - Liu, Benju (2017)
Fil: Liu, Benju. Huazhong University of Science and Technology. Tongji Medical College. Department of Anatomy; China